ANALISIS MANAJEMEN PELAYANAN PERPUSTAKAAN DIGITAL DI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN (BPTP) SULAWESI SELATAN - Anwar Makkasau (UPT Perpustakaaan Universitas Hasanuddin, 2016)
AbstractThis study aims to determine how much influence the quality of the humanresources manager of the library, the availability of information andcommunication technology infrastructure, as well as building infrastructure andlibrary of the quality of service at the library AIAT South Sulawesi. Besides, italso wants to know the dominant factor among the three factors above. Thepopulation in this study are all users of digital libraries AIAT South Sulawesi(researchers, extension workers, research and engineering technicians, BPTPadministration staff, and general users) with a total of 315 people. Samplingwas done by proportionally.The analysis showed that the factor of quality human resources manager of thelibrary, the availability of information and communication technologyinfrastructure, as well as infrastructure building and library have a significanteffect (F = 94.537, with sig = 0,000) with a contribution of 76.3% on theQuality of Service to Digital Library BPTP South Sulawesi, while theremaining 23.7 percent is influenced by other factors. By using a digital systemWinisis.Key words: digital libraries, analytics, services, BPTP Sulsel.